A Comparative Study On Faculty Perception On Online And Offline Teaching (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Change is the only thing that remains constant.Pandemic has created lots of changes in all the sectors.This is especially true in case of education sector. In ancient times, Gurukula system of education was followed in India, in which anyone who wished to study went to a teacher's house and requested to be accepted as their student. The modern education system was brought to India where the curriculum was confined to “modern” subjects.All through the years classes were conducted in physical environment.Due to advancement of technology many changes have taken place in education sector.The concept of e-learning was introduced but not been made as compulsion.But in this Pandemic due to shut down of colleges as there are no possibility for physical classes, online classes in digital platforms have been chosen to avoid disruption in studies for the students. Adaptability to changing scenario is a great task.A sudden drastic shift from physical classes to online classes has been faced by faculty members.Hence it becomes need of an hour to understand faculty’s opinion about online classes. Therefore, an attempt has been made here to study the perception of faculty over online and offline classes. Faculty members of Shri ShankarlalSundarbaiShasun Jain College for Women has been chosen for the purpose of study.Questionnaires were circulated and tools like Mean,t-Test and One-way ANOVA were used to analyse the data collected.